A SYSTEMATIC REVIEW: MECHANISM OF ACTION ORAL AND TOPICAL RETINOL (Retinyl palmitate) AS A THERAPY OF ACNE SKIN IN BEAUTY PRODUCTS - Yanuar, Rizqi Fitria; Indrayudha, Peni (Jurnal Farmasi Sains dan Praktis, 2023)
Acne is one of the dermatological diseases that often appears in adolescence to adulthood. Retinol (retinyl palmitate) is a first-generation vitamin A derivative used for acne therapy by reducing sebum production which can cause acne bacteria to grow. This study aims to determine the effectiveness and safety of oral and topical retinol preparations. The method used in the study is systematic review using the PubMed search engine and google scholar according to keywords using the PICO method. Articles that can be downloaded with a period of 2013-2023 for the next article are downloaded in selection according to the criteria, namely inclusion and exclusion. The results of the selection of inclusion criteria there are 12 journals to discuss the effectiveness and safety related to topical preparations and peroral retinol as anti-products acne. The mechanism of action of topical retinol is to reduce the production of micro-comedones caused by the bacteria Propionibacterium acnes (P. acne) for oral retinol has the mechanism of action works by inhibiting the production of sebum by androgen hormones in the 3-alpha-hydroxysteroid oxidation pathway using the enzyme retinol dehydrogenase to retinaldehyde to be able to dissolve and be delivered at the destination. Oral or topical retinol preparations provide different side effects. Topical retinol has a lower rate of side effects compared to oral retinol. The level of safety and effectiveness of topical retinol preparations is better than oral retinol.